Nanoindentation and strain rate effects on hardness of solder materials - Toh, Jyh Terng. (2009)
In this report, three solder materials, SAC387, Pure Sn and Sn-37Pb, underwent nanoindentation testing for hardness and yield stress values at strain rates 0.01/s, 0.1/s, 1.0/s and 10.0/s using the Continuous Stiffness Measurement (CSM) technique. Results show that all three solder materials are strain rate dependent and show increase in hardness with increasing strain rates. The Power-Law strain rate relationships with hardness have been evaluated from the Holloman Equation for individual solder material. SAC387 and Pure Sn are calculated to have similar strain rate exponents (n) of 0.1761 and 0.2218 respectively. This indicates that both SAC387 and Pure Sn experience similar influence of dynamic hardening effect due to increasing strain rates. Comparatively, Sn-37Pb experiences a relatively smaller influence of strain rate effect due to a smaller strain rate exponent of 0.073. A point to note is that at strain rate of 0.01/s, both SAC387 and Sn-37Pb display similar average hardness values of approximately 0.2GPa. Yield stress value of each solder material is evaluated from the average hardness values obtained using Tabor’s Constant of 3. The Power-Law strain rate relationships with yield stress of each solder material are also evaluated. Similarly, SAC387 and Pure Sn are found to display higher influence of strain rate on hardness and yield stress values as compared to Sn-37Pb. Due to the addition of alloying elements Ag and Cu in SAC387, nanoindentation results at strain rates from 0.01/s to 1.0/s have shown consistently superior mechanical strength as compared to Pure Sn. However, at strain rate of 10.0/s, it was also found that SAC387 and Pure Sn show similar hardness and yield stress values of approximately 0.6MPa. Scanning Electron Microscopy (SEM) and Light-Reflected Microscope have been used to image indentation points on each solder material.